RESTFUL WEB SERVICE UNTUK INTEGRASI SISTEM AKADEMIK DAN PERPUSTAKAAN UNIVERSITAS PERJUANGAN - Randi Rizal; Alam Rahmatulloh (JURNAL ILMIAH INFORMATIKA, 2019)
Perjuangan University is developing an information system in its campus, but the system is partially built. This has resulted in its own problems, there is no connectivity between systems and the difficulty of developing data integration. So that in the business process that occurs many experience difficulties in data synchronization and the amount of duplicate data that must be entered. One solution to overcome this problem is to utilize web service technology. The web service architecture used is REST. REST as a bridge that is able to integrate data in a stateless format. The results of the application of the web service as a backend system are able to integrate the existing academic information systems and library information systems without changing existing structures, programs or architecture. Format data exchange between systems using the JSON format. In addition, officers do not need to input and verify data several times, when the data in the library information system changes automatically in the academic information system the changes are immediately read.